Effect of VS organic loads and buckwheat husk on methane production by anaerobic co-digestion of primary sludge and wheat straw. (1st June 2016) - Elsayed, Mahmoud; Andres, Yves; Blel, Walid; Gad, Ali; Ahmed, Abdelkader
Highlights: Co-digestion of PS, WS, and BH was conducted to evaluate different VS organic loads for an optimal methane production. Co-digestion of PS and WS was optimized using buckwheat husk as a new waste material. Combination of PS, WS, and BH produced higher methane yields than the individual digestion of PS, WS, and BH. The highest CMYs and VS removal rate were achieved at C/N ratios of 10 and 7.50 gVS/L, respectively. The purification process increased the methane content from 58.91–63.05% to 92.46–95.30%. Abstract: An environmentally acceptable disposal of sewage sludge and agro-wastes presents an urgent problem facing many countries. Anaerobic digestion (AD) is a robust and suitable technique for producing renewable energy from wastes. This study aims to improve methane production from anaerobic co-digestion of primary sludge (PS) and wheat straw (WS) depending on their volatile solids (VS) organic load and by adding a proposed waste material of buckwheat husk (BH) based on their carbon to nitrogen (C/N) ratio. Mesophilic anaerobic batch tests were carried out in 500-mL digesters. Individual and six mixtures of PS and WS at different VS organic loads were anaerobically digested to optimize VS load for the greatest gas production. The highest cumulative methane yield (CMYs) occurred with combined substrates at a VS load of 7.50 gVS/L. In general, the optimized organic loads that gave the highest cumulative biogas yield (CBYs) and CMYs were in the range of 6–8 gVS/L. In addition, AD of individual substrates of PS, WS, and BH and of their mixture at different C/N ratios was investigated regarding to the methane yields. Multi-component substrates produced the greatest CMY at a C/N ratio of 10.07. The CMYs was increased by 39.26% when the proposed waste material of buckwheat husk (BH) was added to the different mixtures of PS and WS compared to the co-digestion of PS and WS. Experimental results were approved using statistical analysis by ANOVA test at P -value less than 0.05. Purification of methane and biodegradation of VS were evaluated. The results emphasized positive synergy of anaerobic co-digestion for improving CMY and best feedstock utilization.